Preobrazba podeželja ob slovensko-hrvaški meji - Koščak, Marko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2002)
The transformation of the rural areas along the Slovene - Croatian border was influenced by many reasons, among which the most important was polycentric concept of social demogarphy as well as physical development. After introduction of a border line between Slovenia and Croatia the process of transformation of rural areas have taken on additional issues connected to the problems of border areas and marginal regions and thus are both specific and new for this region. Transformation of rural areas is a permanent process,that affects both the landscape, as well as its functions.
Keywords: Croatia; Hrvaška; obmejna območja; podeželje; prostorski razvoj; regionalni razvoj; rural area; Slovenia; Slovenija